Penerapan Akuntansi Pertanggungjawaban Dalam Penilaian Kinerja Pada Ksp Kopdit Hiro Heling - mutia, Mutia; Nona Dince, Maria; Yecci Noeng, Amanda (Universitas Nusa Nipa Maumere, 2026)
Responsibility accounting is a management accounting system that emphasizes the distribution of authority and responsibility at each responsibility center to support the control and evaluation of organizational performance. There are five requirements for implementing responsibility accounting: organizational structure, budgeting, separation of controllable and uncontrollable costs, account code classification, and responsibility accounting reports. This study aims to understand the implementation of responsibility accounting in performance assessment at KSP Kopdit Hiro Heling. The method used in this study is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. The results show that the implementation of responsibility accounting at KSP Kopdit Hiro Heling is still not effective based on the five indicators of responsibility accounting. This condition impacts the suboptimal performance assessment of responsibility centers.